Synthesis of 3,4,5-Trisubstituted Isoxazoles by the 1,3-Dipolar Cycloaddition Reaction of α-Azido Acrylates and Aromatic Oximes - Hu, Manman; He, Xinwei; Niu, Zhiqiang; Yan, Zhenglei; Zhou, Fuyin; Shang, Yongjia (Synthesis, 2014)
A novel, one-pot, cascade reaction sequence featuring the 1,3-dipolar cycloaddition reaction of α-azido acrylates and aromatic oximes was developed. This procedure provides an efficient, straightforward and metal-free method for the synthesis of 3,4,5-trisubstituted isoxazoles under mild reaction conditions.
Keywords: 1,3-dipolar cycloaddition; α-azido acrylates; aromatic oximes; isoxazoles; one-pot synthesis